Elgar Introduction to Designing Organizations (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Presenting the emergence of new organizational designs in a novel way, this insightful book blends theory and practice to examine major trends and directions, the key ideas that underpin organizational design and how these ideas might be applied.